2013
DOI: 10.1084/jem.20131144
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent loss of Ezh2 and Tet2 cooperates in the pathogenesis of myelodysplastic disorders

Abstract: Deletion of Ezh2 results in transcriptional repression of developmental regulator genes, derepression of oncogenic polycomb targets, and induction of MDS/MPN-like disease in mice that is exacerbated by concurrent deletion of Tet2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 37 publications
8
123
1
Order By: Relevance
“…Recent study has demonstrated cooperative function of Tet2 loss and Flt3 ITD mutations in AML development in vivo through combinatorial epigenetic remodeling of specific genetic loci [73]. In agreement with co-occurrence of TET2 and EZH2 mutations in MDS and MDS/MPN patients, concurrent depletion of Tet2 and Ezh2 in mice developed MDS or MDS/MPN by derepression of oncogenic polycomb targets [74]. In addition, combined Tet2 loss with AML1-ETO leads to fully penetrant AML in vivo, partially due to hypermethylation of enhancer regions thereby silencing tumor suppressors [59,75].…”
Section: Tet2mentioning
confidence: 73%
“…Recent study has demonstrated cooperative function of Tet2 loss and Flt3 ITD mutations in AML development in vivo through combinatorial epigenetic remodeling of specific genetic loci [73]. In agreement with co-occurrence of TET2 and EZH2 mutations in MDS and MDS/MPN patients, concurrent depletion of Tet2 and Ezh2 in mice developed MDS or MDS/MPN by derepression of oncogenic polycomb targets [74]. In addition, combined Tet2 loss with AML1-ETO leads to fully penetrant AML in vivo, partially due to hypermethylation of enhancer regions thereby silencing tumor suppressors [59,75].…”
Section: Tet2mentioning
confidence: 73%
“…Figure 5B-C; supplemental Table 2), and that 35 genes, including known oncogenes targeted by Ezh2, Lmo1, Gcat, and Prss16, 44 were common ( Figure 5D). There were some commonly enriched gene sets, including those involved in activation of the MYC pathway between ΔHmga2/JAK2 V617F and JAK2…”
Section: V617f /Ezh2mentioning
confidence: 99%
“…In contrast to EZH2 mutations seen in lymphoma, those in MPNs tend to be loss-of-function mutations 75 that result in the derepression of a set of genes that includes a number of putative oncogenes (e.g., LMO1 and HOXA9), and are associated with increased HSC self-renewal. 76,77 Mutations of additional sex combs like 1 (ASXL1) are also relatively common in MF. 78 ASXL1, a component of PRC1, is also known to regulate PRC2 and to have a role in the regulation of HOX genes.…”
Section: Mutations In Epigenetic Regulatorsmentioning
confidence: 99%